Factor affecting consumers attitude towards logistics service providers in Kota Bharu, Kelantan - Supingin, Amyediah; Chelakanu, Balamurugan; Chin, Sui Lin (2015)
The third party logistic service are influenced by the consumers behaviors that may affecting the effectiveness of company activities. This research main reasons is to identify the main factor that affecting the consumer behavior towards logistics services providers among 100 respondent that using logistic service providers in Kota Bharu, Kelantan area. A total questionnaires is distributed in that area to help us to get the data. The three independent variable which are service quality, customers satisfaction and advertising are selected by the researcher as the main in influencing their attitude towards logistic service providers. This study also analyze the most affecting factor towards the logistic service providers. The findings in this research is contribute some new important information to the logistic service provider company